2012
DOI: 10.1051/epjpv/2012005
|View full text |Cite
|
Sign up to set email alerts
|

Light induced electrical and macroscopic changes in hydrogenated polymorphous silicon solar cells

Abstract: We report on light-induced electrical and macroscopic changes in hydrogenated polymorphous silicon (pm-Si:H) PIN solar cells. To explain the particular light-soaking behavior of such cells -namely an increase of the open circuit voltage (Voc) and a rapid drop of the short circuit current density (Jsc) -we correlate these effects to changes in hydrogen incorporation and structural properties in the layers of the cells. Numerous techniques such as current-voltage characteristics, infrared spectroscopy, hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(88 reference statements)
4
5
0
Order By: Relevance
“…It was postulated that a reversible change in refractive index by 1–3% is possible. Recently, similar reversible light‐induced behavior has been reported by Kim et al Furthermore, Kuyken et al showed that the non‐linearity of a ‐Si:H nanowire waveguides was unstable during the characterization with a pump‐probe technique at 1550 nm. Surprisingly, this phenomenon can be reversed after annealing at 200 °C for half an hour and this can be continued in cycles.…”
Section: Introductionsupporting
confidence: 73%
“…It was postulated that a reversible change in refractive index by 1–3% is possible. Recently, similar reversible light‐induced behavior has been reported by Kim et al Furthermore, Kuyken et al showed that the non‐linearity of a ‐Si:H nanowire waveguides was unstable during the characterization with a pump‐probe technique at 1550 nm. Surprisingly, this phenomenon can be reversed after annealing at 200 °C for half an hour and this can be continued in cycles.…”
Section: Introductionsupporting
confidence: 73%
“…A possible interpretation is that the polymorphous silicon suffers less from light‐induced degradation than standard amorphous silicon. This is in agreement with specific literature on pm ‐Si:H and generally observed for materials that are deposited close to the transition between a ‐Si:H and μ c ‐Si:H (cf. Section 5).…”
Section: Degradation Kinetics Of Polymorphous Siliconsupporting
confidence: 93%
“…Moreover, polymorphous semiconductors represent a technological advance in the development of IR sensing films, since this kind of materials is more stable against the incident radiation than amorphous semiconductors [8][9][10][11][19][20][21], which are currently used as sensing films in commercial IR detector arrays [4].…”
Section: Resultsmentioning
confidence: 99%
“…The better stability of polymorphous semiconductors over the amorphous counterpart has been demonstrated in the fabrication of thin solar cells [19][20][21], where it has been shown that due to radiation (light soaking) the amorphous film solar cells suffer of degradation and its efficiency is reduced from an initial value, while for polymorphous solar cells the degradation is lower. That degradation is related to weak bonds and stress in the material.…”
Section: Resultsmentioning
confidence: 99%